The Effect of Health Education on reducing blood pressure of hypertensive patients at USU Hospital Medan in 2022 - Indra Agussamad (Science Midwifery, 2022)
Hypertension or high blood pressure is a disease of the heart and blood vessels characterized by an increase in blood pressure. Education is an increase in one's knowledge and abilities through learning techniques or instructions, with the aim of remembering real facts or conditions. The purpose of this research is the effect of health education on reducing patient's blood pressure. This type of research is a correlation analytic type with a quasi-experimental design. The sample in this study were hospitalized patients with a diagnosis of hypertension. The method used is observation. The results of the observation show that the blood pressure measurement of hypertensive patients uses a sphygmomanometer. The t-test obtained a significant value of 0.000, which is smaller than alpha 0.05 or 95% significant. So that Ho is rejected and Ha is accepted, it can be said that there is a significant effect between the blood pressure of hypertensive patients before and before being given health education or information. The conclusion that can be drawn is that education is very influential in reducing the patient's blood pressure because it can increase the patient's sense of comfort. This is a consideration for the health team to provide an in-depth understanding of hypertension.